1998
DOI: 10.1046/j.1365-294x.1998.00498.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of molecular markers to study patterns of genotypic diversity in some invasive alien Fallopia spp. (Polygonaceae)

Abstract: Random amplified polymorphic DNA (RAPDs) and inter‐simple sequence repeats (inter‐SSRs) have been used to study clonal growth and hybridization in some non‐native, gynodioecious, invasive weeds from the genus Fallopia (Polygonaceae). At the study site (the River Kelvin, Glasgow, UK) a single genotype of Japanese knotweed (Fallopia japonica) was detected, consistent with all the individuals sampled being ramets of a single clone. Two genotypes of giant knotweed (F. sachalinensis) were detected, with one genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
71
1
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 14 publications
4
71
1
1
Order By: Relevance
“…We chose to use ISSRs (Zietkiewicz et al, 1994) because they have already been shown to generate sufficient markers to easily identify genotypic diversity in clonal plants (Hollingsworth et al, 1998;Chapman et al, 2000). The incorporation of strategies to minimise the effects of dominance (for a review, see Sales et al, 2001) allow the estimation of F ST values from dominant markers that are concordant with codominant allozyme markers (Aagaard et al, 1998;Jenczewski et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…We chose to use ISSRs (Zietkiewicz et al, 1994) because they have already been shown to generate sufficient markers to easily identify genotypic diversity in clonal plants (Hollingsworth et al, 1998;Chapman et al, 2000). The incorporation of strategies to minimise the effects of dominance (for a review, see Sales et al, 2001) allow the estimation of F ST values from dominant markers that are concordant with codominant allozyme markers (Aagaard et al, 1998;Jenczewski et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…There is a large amount of additional literature on F. japonica covering areas including the ecology of the plant (Beerling et al, 1994;Child and Wade, 2000), its reproductive strategies and capabilities (Brock and Wade, 1992;Beerling et al, 1994;Brock et al, 1995;Hollingsworth and Bailey, 2000;de Waal, 2001;Price et al, 2002;Forman and Kesseli, 2003), management techniques and their effectiveness (Child and de Waal, 1997;Seiger and Merchant, 1997;Child et al, 1998;Dawson and Holland, 1999;Brabec and Pysek, 2000;Hathaway, 2000;Child et al, 2001;Green, 2003), the importance of scale in the interpretation of distribution maps and model output (Collingham et al, 2000;Hulme, 2003;Thuiller et al, 2003), its effects on riparian habitats (Pysek and Prach, 1993;Dawson and Holland, 1999;Tickner et al, 2001) and its genetic makeup and hybridisation (Beerling et al, 1994;Hollingsworth et al, 1998;Kim and Park, 2000). There is also a growing amount of data on the distribution of the plant throughout the British Isles collected for or by groups such as the City and Council of Swansea, the Cornwall Knotweed Forum and the Environment Agency.…”
mentioning
confidence: 99%
“…These floras are, however, subject to serious threats from invading alien species. Introduced plant species now occur in virtually every inhabited part of the world, and a small minority of such plants can become aggressively invasive and displace native species from their habitats (Williamson, 1996;Hollingsworth et al, 1998;Milne and Abbott, 2000;Mooney and Cleland, 2001). The isolated biotas of oceanic tropical islands are particularly vulnerable to invasion by alien species, because they tend to comprise highly adapted specialist rather than generalist species.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrids involving an invasive alien species such as L. robustum might result in the transfer of adaptive traits to the invader through introgression (Rieseberg and Wendel, 1993;Strefeler et al, 1996;Milne and Abbott, 2000), or produce a hybrid lineage more invasive than either parent (Daehler and Strong, 1997;Vila and D'Antonio, 1998;Ellstrand and Schierenbeck, 2000), or that has the potential to be so (Hollingsworth et al, 1998). Two other Ligustrum species, L. sinense and L. ovalifolium, occur as naturalised aliens in La Réunion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation